High-resolution US versus MR neurography for diagnosis of upper extremity peripheral nerve disorders - Fösleitner, Olivia; Kirchner, Marietta; Preisner, Fabian; Kronlage, Moritz; Godel, Tim; Jende, Johann; Hilgenfeld, Tim; Heiland, Sabine; Wick, Wolfgang; Bendszus, Martin; Schwarz, Daniel (Radiology, 2025)
Background - - High-resolution imaging methods help provide important pathologic and morphologic information in diagnosing peripheral nerve disorders, but their diagnostic roles remain unclear due to limited clinical evidence. - - Purpose - - To investigate the diagnostic performance of high-resolution nerve US (HRUS) and MR neurography (MRN). - - Materials and Methods - - This prospective, observational, single-center cohort study included 800 participants who were referred for clinically suspected peripheral neuropathy in the upper extremity from November 2015 to February 2022. Participants underwent both HRUS and MRN, performed and interpreted independently by experienced neuroradiologists. Accuracy, sensitivity, and specificity of HRUS and MRN in correct diagnosis of peripheral neuropathy were calculated in reference to the final diagnosis, based on compound results of clinical, electrophysiologic, imaging, surgical, and histopathologic findings, and compared by using McNemar test and χ2 testing. - - Results - - In total, 800 participants (431 male, 369 female; mean age, 47.8 years ± 16.5) were included. Overall, MRN had higher accuracy (85.4% [95% CI: 82.7, 87.8] vs 70.6% [95% CI: 67.3, 73.8], respectively; P < .001) and sensitivity (91.6% [95% CI: 89.1, 93.7] vs 68.6% [95% CI: 64.8, 72.2], respectively; P < .001), whereas HRUS had higher specificity (76.4% [95% CI: 69.9, 81.8] vs 66.2% [95% CI: 59.1, 72.8], respectively; P < .001) in helping to diagnose peripheral neuropathy. - - Conclusion - - In helping to diagnose peripheral neuropathies in the upper extremity, MRN achieved higher accuracy and sensitivity, whereas HRUS achieved higher specificity. - - © RSNA, 2025 - - Supplemental material is available for this article. - - See also the editorial by Deshmukh in this issue.